2006
DOI: 10.1103/physrevb.73.184518
|View full text |Cite
|
Sign up to set email alerts
|

Fine details of the nodal electronic excitations inBi2Sr2CaCu2O8+

Abstract: Very high energy resolution photoemission experiments on high quality samples of optimally doped Bi2Sr2CaCu2O 8+δ show new features in the low-energy electronic excitations. A marked change in the binding energy and temperature dependence of the near-nodal scattering rates is observed near the superconducting transition temperature, TC. The temperature slope of the scattering rate measured at low energy shows a discontinuity at TC. In the superconducting state, coherent excitations are found with the scatterin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
8
17
0
Order By: Relevance
“…134 ͒ The changes observed in ab are consistent with the idea that the near-nodal states are essential for establishing the phase coherence. 135,136 This behavior also seems consistent with the two-gap behavior that has been identified in underdoped cuprates, 137,138 in which the d-wave-like gap in the near-nodal region can extrapolate to a smaller energy than the gap observed for the antinodal states. It would be quite interesting to see with photoemission whether a gapless nodal arc 139,140 of electronic states is present at the Fermi level for T Ͼ T so .…”
Section: Interpreting the Datasupporting
confidence: 86%
“…134 ͒ The changes observed in ab are consistent with the idea that the near-nodal states are essential for establishing the phase coherence. 135,136 This behavior also seems consistent with the two-gap behavior that has been identified in underdoped cuprates, 137,138 in which the d-wave-like gap in the near-nodal region can extrapolate to a smaller energy than the gap observed for the antinodal states. It would be quite interesting to see with photoemission whether a gapless nodal arc 139,140 of electronic states is present at the Fermi level for T Ͼ T so .…”
Section: Interpreting the Datasupporting
confidence: 86%
“…Because of these changes, the quasiparticle self-energies at low energies are also temperature dependent as shown in Fig. 3(a) for optimally doped BSCCO and in general agreement with previous experiments [6,21,22].…”
supporting
confidence: 90%
“…One can see that the QPW (HWHM) denoted as Γ increases with temperature. An early ARPES study [26] has shown that the QPW around the node in the normal state is proportional to temperature T as a fingerprint of marginal Fermi liquid [27]. Within the experimental resolution of ARPES, Γ versus T is consistent with Γ ∝ T .…”
mentioning
confidence: 81%